Implementing Speech-Texter Application to Improve EFL Learners’ Fricative Pronunciation - Maspufah Maspufah; Diana Zuriati (UIR Press, 2022)
Most of EFL learners in Indonesia hardly adopt pronunciation due to limited time, problem from the role model, and difficult sound production. To solve the problem, speech texter-application was implemented as learning media. The research aimed to identify whether and to what extent implementation of speech-texter application can improve EFL learners’ fricative pronunciation and explain the factors which influence the changes in pronouncing fricative consonants. The research implemented action research method. The research used purposive sampling technique and 16 learners from the first semester of a private public college in Pekanbaru. There were instruments used to collect the data. The quantitative data were pronunciation oral test, while the qualitative data were observation checklist, field note and interview. The qualitative data were analysed by scoring and comparing to the standard ability and qualitative data were analysed by data , data display and conclusion drawing. After analysing the data, it was revealed that speech-texter application was able to improve learners’ fricative pronunciation. The improvement of learners’ ability was from the level of “fair” into “good” category at the end of cycle 1. The factors which affecting the improvement was the use of speech-texter application which provide opportunity as self-check application. Thus, it can be concluded that the implementation of speech-texter.